2020
DOI: 10.3389/fnagi.2020.00137
|View full text |Cite
|
Sign up to set email alerts
|

Dl-3-n-Butylphthalide Promotes Remyelination and Suppresses Inflammation by Regulating AMPK/SIRT1 and STAT3/NF-κB Signaling in Chronic Cerebral Hypoperfusion

Abstract: Demyelination in vascular dementia (VD) is partly attributable to inflammation induced by chronic cerebral hypoperfusion (CCH). Remyelination contributes to the recovery of cognitive impairment by inducing the proliferation and differentiation of oligodendrocyte progenitor cells. It was previously reported that Dl-3-n-butylphthalide (NBP) promotes cognitive improvement. However, whether NBP can stimulate remyelination and suppress inflammation after CCH remains unclear. To answer this question, the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 55 publications
4
19
0
Order By: Relevance
“…Recent studies have shown that enhanced remyelination reverses cognitive dysfunction in a murine model of Alzheimer's disease (Chen et al, 2021a). This finding was also confirmed in the chronic cerebral hypoperfusion rat model (Li et al, 2020). In this study, the down-regulation of MBP caused by anesthetic and surgical factors in the hippocampus of aged mice suggesting the appearance of demyelination.…”
Section: Discussionsupporting
confidence: 80%
“…Recent studies have shown that enhanced remyelination reverses cognitive dysfunction in a murine model of Alzheimer's disease (Chen et al, 2021a). This finding was also confirmed in the chronic cerebral hypoperfusion rat model (Li et al, 2020). In this study, the down-regulation of MBP caused by anesthetic and surgical factors in the hippocampus of aged mice suggesting the appearance of demyelination.…”
Section: Discussionsupporting
confidence: 80%
“…Brain insult in the form of traumatic brain injury (TBI), CH, excitotoxic pathways, and several neurotoxins (free radicals) (Negre-Salvayre et al, 2008) can galvanize the NF-κB action resulting in an upsurge in cell degrading enzymes (e.g., matrix metalloproteinases), cytokines (e.g., IL-6, C-reactive protein), and in ammatory molecules (e.g., selectins, integrins, iNOS, cyclooxygenase-2) (Liu et al, 2017;Duncombe et al, 2017). In harmony with previous conclusions (Li et al, 2020), CH signi cantly enhanced the brain in the existing pre-clinical investigation. Treatment with theobromine (100 mg/kg) attenuated the CH-induced brain NF-κB levels that might have contributed to lowering in ammatory cytokines (TNF-α, IL-1β, IL-6).…”
Section: Discussionsupporting
confidence: 68%
“… 20 Similar results have been found in vascular dementia. 21 Further linking AMPK and our previous work on HMGB1 regulation, we found novel information regarding IGFBP-3 and AMPK in RECs. Our findings agree with studies involving 3T3 cells and mice on a high-fat diet that found that Lactobacillus plantarum (Ln4) could increase both IGFBP-3 levels and AMPK actions.…”
Section: Discussionsupporting
confidence: 58%